Prescription of psychotropic drugs in patients with chronic renal failure on hemodialysis. (November 2014) - Yeh, Chou-Yu; Chen, Chih-Ken; Hsu, Heng-Jung; Wu, I-Wen; Sun, Chiao-Yin; Chou, Chia-Chi; Lee, Chin-Chan; Wang, Liang-Jen
Abstract Objective: Patients on hemodialysis commonly have comorbid depression and require treatment with psychotropic drugs. This study aimed to investigate the prevalence of the use of psychotropic drugs among patients on hemodialysis and to elucidate the factors associated with use of each class of psychotropic medication. Methods: This cross-sectional study enrolled 195 hemodialysis patients with a mean age of 58.5 years. Patients were assessed using the Mini International Neuropsychiatric Interview, Hospital Anxiety and Depression Scale, Chalder Fatigue Scale and Short-form Health-related Quality of Life. We analyzed the frequency of psychiatric outpatient department visits within six months prior to interview and psychotropic drugs use within one month prior to interview, including antidepressants, antipsychotics, mood stabilizers, benzodiazepines (BZDs) and hypnotics. Results: Of the 195 patients, 47 (24.1%) fulfilled the DSM-IV criteria for major depressive disorder (MDD). Only 6.4% of patients diagnosed with MDD visited the psychiatry outpatient department within six months prior to interview. Of the total patients, the proportions with use of antidepressants, antipsychotics, mood stabilizers, BZDs and hypnotics were 5.6%, 1.0%, 3.1%, 42.6% and 20.0%, respectively. Having MDD was an independent factor associated with taking antidepressants (adjusted OR = 3.98, p = 0.036) and taking hypnotics (adjusted OR = 2.75, p = 0.011). Conclusions: Depression is generally undetected or not well-managed among hemodialysis patients in the clinical setting. Only a small proportion of depressed patients received antidepressant treatment. BZDs and/or hypnotics might be exorbitantly prescribed. Clinicians should pay more attention to patients' emotional distress and provide appropriate treatment.